Quality of Life in Patients with Acromegaly before and after Transsphenoidal Surgical Resection. (4th August 2020) - Gu, Jing; Xiang, Shiyuan; He, Min; Wang, Meng; Gu, Yanfang; Li, Lingjuan; Yin, Zhiwen
Abstract : Objective . We aimed to determine the perioperative changes in the quality of life (QoL) in patients with acromegaly and to reveal the relationship between biochemical indicators and quality of life change after tumor resection. Methods . Patients with acromegaly were enrolled from a tertiary pituitary center. SF-36 scale and AcroQoL scale were used to determine the QoL before and after surgery. We analyzed changes in QoL using a generalized linear model for repeated measurements. We compared the changes in QoL among three groups (remission, active, and discordant group) based on postoperative growth hormone (GH) and insulin-like growth factor-1. Results . 151 patients (75 males and 76 females) diagnosed with acromegaly were included. The average age was 43.9 ± 12.3 years. The median total SF-36 scale was 65.3% (IQR: 63.2%–69.2%). Overall AcroQoL score at baseline was 59.1% (IQR: 51.8%–71.8%). Nadir GH levels (coefficient −0.08, p = 0.047 ), T3 levels (coefficient 2.8, p = 0.001 ), and testosterone levels (coefficient −0.20, p = 0.033 ) in males were independent predictive factors of the total SF-36 score. During the follow-up, the median overall SF-36 score increased to 66.1% at 3 months and 75.3% at 6 months (p < 0.001 ) after surgery. The median overall AcroQoL score increased to 74.5% at 3 months and 77.3% at 6 months (p < 0.001 ) after surgery. At 6-month follow-up, median scores were still less than 70% in appearance, vitality, and mental health dimensions. The QoL after surgery were similar among the three groups, although higher GH and more preoperative somatostatin analogs usage were observed in the active group. Conclusion . In conclusion, acromegalic patients were associated with low QoL, which could be reversed partially by surgery. The improvement was independent of the endocrine remission. Appearance, vitality, and mental health were three major aspects that warrant further attention from physicians and caregivers after surgery.